A simple calibration of Hobo 4 channel analogue dataloggers for use with Watermark 253–L soil water potential sensors - Kaptein, Nkosinathi D; Titshall, Louis W (Water SA, 2019)
The combination of granular matrix sensors with a Hobo 4 analogue channel datalogger provides a relatively inexpensive continuous soil water monitoring system. However, the datalogger excites all 4 channels concomitantly as it reads the sensor measurement of each channel in sequence. This results in localised electrolysis causing measurement bias error in Channels 2, 3 and 4. To evaluate this channel bias, Watermark granular matrix sensors were connected to Hobo 4 channel dataloggers to measure electrical conductance of the soil. This study formed part of a larger study aimed at understanding water use by Eucalyptus plantations at different soil depths. The measured soil conductivity was calibrated against the gravimetric method in soil derived from Natal Group Sandstone and Dwyka Tillite that occur in southern KwaZulu-Natal. The channels of a Hobo 4 channel datalogger were successfully calibrated against the gravimetric method for both soil types (R2 > 0.92). The voltage measurements of each channel increased in the order 1 < 2 < 3 < 4 for both soil types at a soil water content range of 12 to 44% and 6 to 46% for Dwyka Tillite and Natal Group Sandstone soils, respectively. Channel measurements were similar at soil water content ranges below 12 and 6% for tillite and sandstone soils, respectively. The study showed that Channels 2, 3 and 4 of the Hobo 4 channel datalogger are affected by electrolysis. If this analogue datalogger is used with these types of sensors, these channels need to be calibrated back to Channel 1.